Penatalaksanaan Ortodontik Gigi Insisivus Sentralis Kiri Atas dengan Impaksi Inverted - Purwanty Nancy; Sri Kuswandari; Raharjo (Denta Journal Kedokteran Gigi, 2016)
Introduction: Upper anterior inverted impaction were common condition affecting the anterior side of upper jaw due to traumatic condition on the period of early stage of tooth development (decidui stage). This condition were successfully managed to create un-erupted replacement tooth and to stepping back the condition onto the previous track, the intervention of occlusal retraction with ligature wire is necessary needed. Purpose: The aim of this study was to elaborate the orthodontic treatment with inverted impaction. Case: A boy aged of 11 years and 2 months was coming to the clinic with final diagnose of 21 with inverted impaction. Case management: Fixed edgewise orthodontic appliance were applied on incisivus until first molar upper jaw continued by impacted exposure surgery on 21 then followed by application of button at the surface of palatal side then connected by the wire. The appliance were activated each three weeks. After 17 months, the treatment were successfully created new inclination into 120 degree to the normal occlusion surface. The vitality test has been performed and show good result. Conclusion: A treatment of 21 withinverted impacted condition on the young boy of aged of 11 years and 2 months were manageable by fixed edgewise orthodontic appliance post exposure surgery with retraction of ligature wire.